The Performance of the Palestinian Industry: An Econometric Analysis of Industrial Production function 1994-2000 - Gaber Abu-Gamea (My University, 2008)
This study evaluates the performance of the Palestinian industrial sector for the period 1994-2000. It sets an industrial Cobb-Douglas production connecting production to fixed capital investment and labor. The study uses panel analysis methodology throughout fixed-random effects procedures. Mainly, empirical results of fixed effects indicate the existence of heterogeneity among industries. Evidence on this heterogeneity is given by introducing dummy variables in production equation. Distinctively, random-effects result shows that the Palestinian industry slightly surpassed constant returns to scale, a situation reflecting a limited improvement for industry within this period. Generally, empirical results show a relatively marginal impact of capital on industrial production compared with a significant influential one for labor force, a situation reflecting the dependence of industrial production on labor and weakness of industry capital capabilities. Overall, these results reveal a potential ability of the Palestinian industry for a better performance with an expected favorable industrial environment in future.

تقيم هذه الدراسة أداء الصناعة الفلسطينية للفترة ما بين 1994- 2000. ولهذا الغرض ترسي الدراسة دالة كوب - دوغلاس للإنتاج الصناعي التي تربط بين الإنتاج وكل من الاستثمارات الرأسمالية الثابتة والعمالة الصناعية. وتستخدم الدراسة طريقة ترابيع البيانات (Panel data) في التحليل القياسي لهذه الدالة، وذلك من خلال كل من إجرائي التأثيرات الثابتة والعشوائية. بشكل رئيس تشير نتائج التحليل العملية لإجراء التأثيرات الثابتة إلى معنوية عدم التجانس في الجزء الثابت للصناعات المختلفة. وقد تم الاستدلال على الفروقات الفردية بين الصناعات المختلفة بإدخال متغيرات وهمية لمعادلة الإنتاج الصناعي. كما ويظهر تحليل التأثيرات العشوائية، على نحو مميز، تجاوز الصناعة الفلسطينية لوضع ثبات الغلة على نحو ضئيل، الأمر الذي يعكس نتيجة التحسن في الأداء الصناعي خلال فترة الدراسة. وبينما يظهر التحليل القياسي بشكل عام ضعف تأثير الاستثمارات الرأسمالية على الإنتاج، فإن حجم العمالة الصناعية كان المؤثر المعنوي الرئيس إحصائياً على هذا الإنتاج، الأمر الذي يعكس ضعف القدرات الرأسمالية أو الاستفادة منها في حالة الصناعة الفلسطينية. هذا وتوحي نتيجة التحسن في الأداء الصناعي خلال هذه الفترة إلى إمكانية التقدم في هذا الأداء مع حدوث بيئة مواتية في هذا القطاع. الكلمات المفتاحية: دالة الإنتاج كوب - دوغلاس الصناعية، طريقة ترابيع البيانات، التأثيرات الثابتة والعشوائية
أداء الصناعة الفلسطينية: التحليل القياسي لدالة الإنتاج الصناعي - الفترة ما بين1994-2000